2020
DOI: 10.1097/corr.0000000000001356
|View full text |Cite
|
Sign up to set email alerts
|

Do 3-D Printed Handheld Models Improve Surgeon Reliability for Recognition of Intraarticular Distal Radius Fracture Characteristics?

Abstract: Background For fracture care, radiographs and two-dimensional (2-D) and three-dimensional (3-D) CT are primarily used for preoperative planning and postoperative evaluation. Intraarticular distal radius fractures are technically challenging to treat, and meticulous preoperative planning is paramount to improve the patient’s outcome. Three-dimensionally printed handheld models might improve the surgeon’s interpretation of specific fracture characteristics and patterns preoperatively and could theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Compared to Langerhuizen et al 11 who observed no improvement in the reliability for classifying fracture characteristics of AO/OTA types B and C distal radius fractures with 3D printed models, we achieved satisfactory results for evaluating the morphology and preoperative planning for AO/OTA type C distal radius fractures, with an improved overall intra-observer agreement from fair to moderate for the AO/OTA classification and questions: “How many fragments are dislocated?” and “How many fragments have to be fixed?” ( P < .05). In the overall inter-observer agreement, the kappa values improved from slight to fair for the questions “How many fragments are dislocated?” and “How many fragments have to be fixed?” ( P < .05).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Compared to Langerhuizen et al 11 who observed no improvement in the reliability for classifying fracture characteristics of AO/OTA types B and C distal radius fractures with 3D printed models, we achieved satisfactory results for evaluating the morphology and preoperative planning for AO/OTA type C distal radius fractures, with an improved overall intra-observer agreement from fair to moderate for the AO/OTA classification and questions: “How many fragments are dislocated?” and “How many fragments have to be fixed?” ( P < .05). In the overall inter-observer agreement, the kappa values improved from slight to fair for the questions “How many fragments are dislocated?” and “How many fragments have to be fixed?” ( P < .05).…”
Section: Discussionmentioning
confidence: 47%
“… 10 In contrast, another study where 3D printed models were added has reported no improvements in reliability for the recognition of fracture characteristics and classification of AO/OTA B type C distal radius fractures. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Forty-four patients without a good-quality preoperative CT scan and those with a bone disease (such as osteoporosis or osteogenesis imperfecta) were excluded. Previous studies on the additional value of 3D-printed models were based on approximately 20 fractures and could not demonstrate a clinically relevant improvement [ 2 , 11 ]. To ensure that observers could stay focused during the classification process and that a possible clinically relevant improvement could be achieved, we decided to include 40 patients with a tibial plateau fracture.…”
Section: Methodsmentioning
confidence: 99%
“…The value of 3D-printed models in classifying and assessing fractures is controversial. Studies on intraarticular distal radius fractures and distal humerus fractures show that 3D-printed models do not improve interobserver agreement [ 1 , 11 ]. A similar study on acetabular fractures demonstrated that 3D-printed models improve interobserver agreement in classification compared with conventional radiographs, but not compared with CT [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given such disadvantages, attention has turned to other approaches better able to address these issues [ 9 ]. Recently, 3-dimensional (3D) printing has been introduced, and found to be useful in many areas of medicine [ 10 ]. For example, Zhou et al reported the application of a 3D-printed template to assist sacroiliac screw placement, improving the operation’s safety profile [ 11 ].…”
Section: Introductionmentioning
confidence: 99%